Penggunaan Billy Blanket Pada Neonatus Dalam Menurunkan Kadar Bilirubin - Grace Issabella Ambarita; Lina Dewi Anggraeni (Universitas Faletehan, 2019)
Hyperbilirubinemia is increased levels of bilirubin in the blood, which is on the mark with icteric. The condition can lead to prolonged hyperbilirubinemia kernicterus that is the state of the damage to the brain due to adhesions of bilirubin levels in the brain. This research aims to know the description of bilirubin levels decrease with the use of a Billy Blanket in neonates at X hospital Jakarta. The research method used is descriptive analytic with quantitative design. This research population numbered 60 respondents. The sampling techniques used are the total sampling. The secondary data were obtained from patients’ medical records and were analyzed through an analysis univariate to find out the frequency distribution of characteristics and decreased neonates bilirubin levels using Billy Blanket. Majority of respondents characteristic sex male were 51.7%, respondents was born at ≥ 37 weeks gestational age were 73.3%, respondents aged 2 days were 40% and all of the respondents have BBL≥2500 grams. The results showed that levels of bilirubin after using a Billy Blanket for 24 hours and 48 hours of 100% of the respondents have the levels of bilirubin > 10 g/dl during the 72 hours while most respondents 51.7% had levels of bilirubin 5-10 g/dl. The use of a Billy Blanket may be considered to be one of the nursing interventions nursing care so that more optimal.